DIGITAL RESILIENCE OF MUSLIM STUDENTS IN FACING DISTRACTIONS OF MENTAL HEALTH STUDIES - Heru Budiansyah; Fitriah M. Suud (World Psychology, 2026)
The development of digital technology has presented various forms of distractions that affect the academic, social, and spiritual lives of Muslim students. This research aims to analyze the form of digital distraction, its impact on mental health, and the role of digital resilience in helping Muslim students face technological pressure in the Society 5.0 era. The study used a descriptive qualitative approach with interview techniques on 10 Muslim. The results show that the dominant forms of digital distraction include academic procrastination, infinite scrolling, postponement of worship, digital anxiety (FOMO), and decreased quality of social interaction. These distractions have an impact on increased academic stress, cognitive fatigue, emotional anxiety, and low student self-control. This study also found that digital resilience based on Islamic values is able to help students reduce the negative impact of technology through self-regulation, digital detox, digital literacy, social support, and spiritual strengthening such as prayer, dhikr, and reading the Qur’an. Thus, digital resilience is an important foundation in maintaining the mental health of Muslim students in the midst of increasingly complex digital technology developments.